RESOLUÇÃO DE PROBLEMAS EM OSCILAÇÕES E ONDAS: UMA ABORDAGEM PARA O ENSINO MÉDIO - Nero, Harnye Del (2007)
One of the most challenging point on the Physics Learning studies are to make the students fascinating and critical in front of phenomenon and techniques related with their quotidian. Besides that, we have a high stalemate with the theory and the process involved to understand the Physics laws associated with these techniques. In this way, the method of resolution problems is considered an interesting strategy to approximate the Physics contents with the student s reality. Than, we present a communication of the experience about the development and application of didactic lessons with the methodology of the problem resolution on the Secondary School associated with the oscillation and waves themes. We develop didactic lessons related with equipments or physics phenomenon near the quotidian of the students. These lessons also present Internet pages, previously selected, with multimedia texts, virtual simulations and videos. This proposal was applied in four (04) classes of the Second year of the Secondary School of Sant´Anna of Santa Maria RS, with a total of 156 students. In each class, the didactic activities are differentiated with the aim to evaluate the involvement and the behavior of the student in front of this methodology. Than, we verify that the methodology of resolution problems associated with oscillation and waves generate several questions and discussions related with the Physics laws present on the activities. The students change their behavior, looking for new knowledge additional what were exposed on the class. And, finally, some students became able to do connections with the contents and your quotidian.